2021
DOI: 10.3389/fpls.2021.674327
|View full text |Cite
|
Sign up to set email alerts
|

Australian Lentil Breeding Between 1988 and 2019 Has Delivered Greater Yield Gain Under Stress Than Under High-Yield Conditions

Abstract: The contemporary lentil (Lens culinaris ssp. culinaris) industry in Australia started in the late 1980s. Yield in farmers’ fields averages 1.2 t ha–1 nationally and has not increased over three decades. Lack of yield progress can be related to a number of non-mutually exclusive reasons: expansion of lentil to low-yielding environments, lack of genetic gain in yield, lack of progress in agronomic practices, and lack of adoption of superior technologies. The aims of this study were to (i) quantify the genetic ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(63 reference statements)
2
10
0
Order By: Relevance
“…Our study from 2 years data indicated a lentil yield increase of 1.1% per annum. This is in agreement with previously reported by Sadras et al (2021) at Roseworthy, South Australia and by Bogale et al (2017), in Ethiopia. Our data support the previous studies, but also indicates some changes in morpho-physiological traits related to radiation capture and photosynthesis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study from 2 years data indicated a lentil yield increase of 1.1% per annum. This is in agreement with previously reported by Sadras et al (2021) at Roseworthy, South Australia and by Bogale et al (2017), in Ethiopia. Our data support the previous studies, but also indicates some changes in morpho-physiological traits related to radiation capture and photosynthesis.…”
Section: Discussionsupporting
confidence: 94%
“…Genetic yield increases have also been related to phenology, particularly in environments experiencing severe water stress with yield ≤560 kg ha −1 as indicate by Lake and Sadras (2021) and reinforces our study. New lentil cultivars adapted for Australia have earlier flowering and longer grain filling periods than older cultivars ( Lake and Sadras, 2021 ; Sadras et al, 2021 ). Our study also supports the increase in yield gains.…”
Section: Discussionmentioning
confidence: 99%
“…Outside these traditionally more favorable cropping areas, lentil production remains small partly due to a lack of adapted genotypes and absence of knowledge on tailored, locally relevant agronomic and management practices. Over the years, the Australian lentil breeding program has been selecting for early maturing varieties to minimize the impact of abiotic stresses and match developmental stages with the available resources [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, lentils are grown mostly under dryland conditions in areas with low and variable seasonal rainfall and as a result, commonly suffer moisture stress, especially in arid years. Production is mostly concentrated in Victoria and the mid-north of South Australia on mostly alkaline soils, and yields are on average 1200 kg ha −1 [26,27]. Overall, lentils are cultivated on an area of over 412,381 ha, and produce about 525,848 t total grain per annum [27].…”
Section: Introductionmentioning
confidence: 99%